Седиментації смислів у культурі та відповідальність пам'яті - Іванова-Георгієвська, Н. (Інститут філософії ім. Г.С. Сковороди НАН України, 2009)
The contemporary situation of «returning to the source» to search for the main meanings calls for responsibility of memory. This article aims to explain some problems of formation of meanings and their performance on the ground of Husserl's and some his followers' phenomenological methodology, such as schemes and factors of devastation of meaning as a result of the sedimentations of meanings in the culture. The formation of simulated meanings is connected with such impacts as linguistic expression of acts of constitution of meanings; factors of memory manipulation; reactivation of meaning completeness through a return to primary meaning. The memory is a main instrument in the conservation of a true sense of the past. This requires reinterpretation of historical events and implication of unknown facts in order to overcome the mythologized notions and apprehensions of the past. In conclusion, the author contends that memory isn't a can of invariable meanings but is a living organism urged to reactivate and to create adequate understanding of history by means of revealing the true senses accessible to the human mind.